2009
DOI: 10.1007/s10637-009-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

FBA-TPQ, a novel marine-derived compound as experimental therapy for prostate cancer

Abstract: We recently synthesized a series of novel makaluvamine compounds, and found that the most potent was FBA-TPQ. The effects of FBA-TPQ on human (LNCaP and PC3) and murine (TRAMP C1) prostate cancer cells were evaluated. Potential mechanisms of action of the compound were also determined. FBA-TPQ exhibited dose-dependent cytotoxicity in the low micromolar range, inhibited proliferation, caused cell cycle arrest, and induced apoptosis in prostate cancer cell lines. The compound also decreased the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Previous studies indicated that BA-TPQ had activity against various human cancer cell lines, and that it was especially effective against breast cancer cells [13-15]. The mechanism(s) of action of BA-TPQ were not examined previously, but studies of related compounds have indicated various possible mechanisms of action for the iminoquinone analogs, including inhibition of topoisomerase II, inhibition of cell survival/proliferation, inhibition of oncogene expression, and interference with hormone receptor signaling [13-15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that BA-TPQ had activity against various human cancer cell lines, and that it was especially effective against breast cancer cells [13-15]. The mechanism(s) of action of BA-TPQ were not examined previously, but studies of related compounds have indicated various possible mechanisms of action for the iminoquinone analogs, including inhibition of topoisomerase II, inhibition of cell survival/proliferation, inhibition of oncogene expression, and interference with hormone receptor signaling [13-15].…”
Section: Discussionmentioning
confidence: 99%
“…1a. In accord with studies of other natural-product based agents, the iminoquinone analogs exert a variety of anti-cancer activities, including inhibition of topoisomerase II [14], inhibition of cell survival/proliferation [13], inhibition of oncogene expression [15], and inhibition of androgen receptor expression [15]. Because preliminary studies indicated that BA-TPQ was highly effective against breast cancer cells [13, 14], the present study examined the compound’s in vivo anti-breast cancer activity, and further examine the mechanism(s) by which it exerts anti-cancer effects in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…After two weeks of selection with G418 (Invitrogen, Carlsbad, CA), the cells stably expressing PSA-luc were amplified and referred to as LN-PSA-luc. Luciferase reporter assay was carried out as previously described (42). Briefly, the cells were seeded in complete growth medium and were allowed to grow to 40–50% confluence, and then were fed phenol red-free RPMI1640 medium supplemented with 10% charcoal-stripped serum for 24h.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the BA-TPQ inhibition of tumor growth through down-regulation of MDM2 expression is independent of p53 status, demonstrating a broader range of anti-tumor effect even for the p53 mutant cancer cell lines [7]. However, despite its high potency against a variety of human cancer cell lines including breast and prostate tumors [8,9], the application of BA-TPQ has been limited by its poor solubility and low bioavailability. In addition, undesirable toxicity was observed in mice after administering BA-TPQ (a formulation of dispersed BA-TPQ in a mixture of PEG400/ethanol/0.9% saline [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its high potency against a variety of human cancer cell lines including breast and prostate tumors [8,9], the application of BA-TPQ has been limited by its poor solubility and low bioavailability. In addition, undesirable toxicity was observed in mice after administering BA-TPQ (a formulation of dispersed BA-TPQ in a mixture of PEG400/ethanol/0.9% saline [8,9]. Recent investigations identifying the potential sites of accumulation to elucidate the observed BA-TPQ toxicity have revealed a high accumulation of BA-TPQ in the lungs, kidneys, and spleen of the mice [10,11].…”
Section: Introductionmentioning
confidence: 99%